Handbook of meat, poultry and seafood quality - Nollet, Leo M. L. , 1948- (Chichester, West Sussex : Wiley-Blackwell, 2012)
The second edition of Handbook of Meat, Poultry and Seafood Quality, focuses exclusively on quality aspects of products of animal origin, in depth discussions and recent developments in beef, pork, poultry, and seafood quality, updated sensory evaluation of different meat products, revised microbiological aspects of different meat products
1. Quality aspects of products of animal origin -- 2. Flavor -- 3. Beef quality -- 4. Pork quality -- 5. Poultry quality -- 6. Seafood quality
Includes bibliographical references and index
Keywords: Meat -- Quality -- Handbooks, manuals, etc; Poultry -- Quality -- Handbooks, manuals, etc; Seafood -- Quality -- Handbooks, manuals, etc